(untitled) (Bangladesh Journal of Medical Microbiology, 2016)
Recently, in Bangladesh, Chikungunya (CHIK) infection emerged as an important public health issue. Previously, it was not routinely tested by the physician, thus it might remain undiagnosed. Therefore, the present study was undertaken to find out Chikungunya infection in Holy Family Hospital, Dhaka among clinically suspected cases who were sent by the clinicians during rainy season. For detection of Chikungunya infection, a total of 147 serum samples were tested for IgM and IgG of Chikungunya virus (CHIKV) by Immuno chromatographic test (ICT). Out of which 64 (43.5%) samples were positive for Chikungunya infection (positive defined as a person with IgM and or IgG antibody). Of the 64 sero-positive cases, 34 (53.1%), 6 (9.4%) and 24 (37.5%) were positive for only IgM, only IgG and both IgM & IgG antibody respectively. Male were affected higher (51.56%) than female (48.44%). The infection was more common in 31-45 years, 46-60 years and more than 60 years of age groups which was 26.6%, 25% and 26.6% respectively In this study, it was found that among suspected cases of Chikungunya, sero positive cases were 43.5% which was about half of the suspected cases. This finding suggests that, there is need of screening of chikungunya virus and also need of appropriate strategies to control the disease as early as possible. Bangladesh J Med Microbiol 2016; 10 (2): 14-17